PI(3,4)P2-mediated cytokinetic abscission prevents early senescence and cataract formation - Gulluni, Federico; Prever, Lorenzo; Li, Huayi; Krafcikova, Petra; Corrado, Ilaria; Lo, Wen-Ting; Margaria, Jean Piero; Chen, Anlu; De Santis, Maria Chiara; Cnudde, Sophie J; Fogerty, Joseph; Yuan, Alex; et al. (Science, 2021)
[Figure: see text].
Keywords: endozomální třídící komplexy pro transport; Zebrafish; proteiny dánia pruhovaného; Cataract; Cell Cycle Proteins; buněčné linie; lidé; dánio pruhované; Lens, Crystalline; cytokineze; Cellular Senescence; Cell Line; Phosphatidylinositol 4,5-Diphosphate; Phosphatidylinositols; proteiny buněčného cyklu; Mutation; stárnutí buněk; Calcium-Binding Proteins; biologická evoluce; fosfatidylinositoly; myši; Endosomal Sorting Complexes Required for Transport; Humans; Aging, Premature; Mice; mutace; Phosphatidylinositol 3-Kinases; zvířata; fosfatidylinositol-4,5-difosfát; proteiny vázající vápník; oční čočka; předčasné stárnutí; fosfatidylinositol-3-kinasy; Tubulin; Animals; Biological Evolution; katarakta; tubulin; Cytokinesis; Zebrafish Proteins